Guidelines to enhance the psychosocial wellbeing of the San community living at Platfontein in the Northern Cape Province - Angela K. Louw; Izanette Van Schalkwyk (Social Work and Society, 2021)
It is important to develop evidence-based, culturally sensitive interventions in low-and middle-income countries. Information is needed to implement such interventions with the San people living in Platfontein in the Northern Province of South Africa. Within an ecological stance, we aim to accommodate a strengths-based perspective to promote the psychosocial wellbeing of this particular San community. Taking into account recent South African research, guidelines are offered to design an intervention programme emphasizing the role of protective factors and community empowering structures. In this process the importance of"collective wisdom" is underlined, particularly in this San community where realities are associated with chronic risk and population trauma. Therefore, these guidelines emphasise the protection of the inherent dignity and"glorious legacy" of the San. While a first-rate level of cooperation between government, civil society, and the corporate sector is needed to address these complex challenges, the role of social workers can be crucial.